2014
DOI: 10.1104/pp.114.248625
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional, Posttranscriptional, and Posttranslational Regulation of SHOOT MERISTEMLESS Gene Expression in Arabidopsis Determines Gene Function in the Shoot Apex

Abstract: The activity of SHOOT MERISTEMLESS (STM) is required for the functioning of the shoot apical meristem (SAM). STM is expressed in the SAM but is down-regulated at the site of leaf initiation. STM is also required for the formation of compound leaves. However, how the activity of STM is regulated at the transcriptional, posttranscriptional, and posttranslational levels is poorly understood. We previously found two conserved noncoding sequences in the promoters of STM-like genes across angiosperms, the K-box and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 149 publications
(172 reference statements)
3
21
0
Order By: Relevance
“…Therefore, it is possible that the STM originated at an earlier stage in the evolution of dicotyledons, and was lost in monocotyledons. In Arabidopsis and other higher plants, the STM gene is highly expressed in SAM (Elhiti et al, 2013 ; Stammler et al, 2013 ; Aguilar-Martinez et al, 2015 ). In G. max , two STM homologs are strongly expressed in the SAM and others are not specific to SAM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the STM originated at an earlier stage in the evolution of dicotyledons, and was lost in monocotyledons. In Arabidopsis and other higher plants, the STM gene is highly expressed in SAM (Elhiti et al, 2013 ; Stammler et al, 2013 ; Aguilar-Martinez et al, 2015 ). In G. max , two STM homologs are strongly expressed in the SAM and others are not specific to SAM.…”
Section: Discussionmentioning
confidence: 99%
“…4B,C). Among them are the GeBP, FARL, NAC, and Homeobox (HB) TFs, which have a demonstrated link to meristem function (Vollbrecht et al 2000;Aida and Tasaka 2006;Chevalier et al 2008;Aguilar-Martínez et al 2014). Mean expression for the remaining six families is negatively correlated with PC1, suggesting that they act as repressors of meristem identity and/or promote organogenesis.…”
Section: Complex Tf Signatures Drive Cell Identitiesmentioning
confidence: 99%
“…Recent studies have demonstrated that FHY3 and FAR1 play multiple roles in a wide range of cellular processes, including light signal transduction, photomorphogenesis ( Wang and Deng, 2002 ; Lin et al, 2007 ), circadian clock and flowering time regulation ( Li et al, 2011 ), shoot meristem and floral development ( Li et al, 2016 ), chloroplast division ( Ouyang et al, 2011 ), chlorophyll biosynthesis ( Tang et al, 2012 ), starch synthesis ( Ma et al, 2017 ), abscisic acid responses ( Tang et al, 2013 ), oxidative stress responses ( Ma et al, 2016 ), plant immunity ( Wang et al, 2016 ), and the low-phosphate response ( Liu Y. et al, 2017 ), indicating that FHY3 and FAR1 are crucial for plant growth and development ( Table 1 ). In addition, 12 FAR1-RELATED SEQUENCE (FRS) and four FRS-RELATED FACTOR (FRF) family proteins were identified in Arabidopsis thaliana ( Lin and Wang, 2004 ; Aguilar-Martinez et al, 2015 ). Besides FHY3 and FAR1, the physiological and molecular mechanisms of most FRS and FRF family proteins remain largely unknown in plants.…”
Section: Introductionmentioning
confidence: 99%